Percolation and leaching of nutrients in banana soils to the East of the Reventazón river, Limón, Costa Rica. - Acón-Ho, Jorge; Alpízar-Oses, Luis; WingChing-Jones, Rodolfo (Agronomía Mesoamericana, 2013)
The objective of this study was to detwermine leaching losses of Ca, Mg, K and nitric N in banana soils. The work was conducted between 2003-2004 in the Venecia Farm in Matina, Limón, Costa Rica. Three nitrogen fertilizer sources were used: urea (U), ammonium nitrate (aN) and ammonium sulfate (HS). Sampling was conducted at a depth of 60 cm using lysimeters and the volume of percolated water (D) was calculated using the indirect method of soil water balance (BHs). Irrespective of the sampling dates no statistical differences were determined found for pH. The concentration of calcium (Ca) in the leachate for different treatments during different times of sampling, was not significant, but significant differences were found between treatment with U with respect to treatment of NA and SA. No differences between the NA and SA or in the average concentrations of magnesium (Mg) and potassium (K) in the leachate were observed. In the case of nitric nitrogen, significant differences were detected only between the NA regarding the U and SA, both in general and between sampling dates.